Kingdom of the Netherlands-Netherlands Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper for the Kingdom of the Netherlands-Netherlands underlies recent fiscal developments. Fiscal deterioration during economic slowdowns is not unusual and can be justified on economic grounds. Although the real spending ceilings were largely adhered to, procyclical elements embedded in the fiscal framework contributed to the structural fiscal deterioration. Sharp declines in the revenues from corporate profit taxes and social security contributions, as well as increases in social security spending, were largely responsible for the cyclical deterioration.